Changes in Body Weight and Serum Albumin Levels in Patients Requiring Home Long-term Oxygen Therapy - Naomi Kayauchi; Katsunori Kagohashi; Hiroaki Satoh (JMIR Publications, 2021)
Purpose: To investigate the long-term changes in body weight and serum albumin levels in patients with respiratory failure, and those with chronic heart failure, who were treated with home long-term oxygen therapy (LTOT) to understand the current status and contribute to future measures. Methods: Patients with chronic obstructive pulmonary disease (COPD), those with interstitial pneumonia (IP), and those with chronic heart failure (CHF) undergoing home LTOT for 6 months or more between January 2011 and January 2019 were included in the study. Body weight and serum albumin levels were assessed at the start of home LTOT and at the end of the observation period, a minimum of 6 months after commencing home LTOT. Results: Sixty-two patients (29 COPDs, 23 IPs, and 10 CHFs) were included. In COPD patients and IP patients, body weight decreased (P = 0.0017, P = 0.0018, respectively, Wilcoxon signed-rank test). Serum albumin levels decreased in IP patients (P = 0.0185) but not in COPD patients. There was neither significant decrease in body weight nor serum albumin levels in patients with CHF. Conclusion: Chronic respiratory failure patients who have home LTOT were likely to have a decreased nutritional status. In order to provide prolonged home LTOT, medical staff need to pay close attention to the nutritional status of patients receiving home LTOT.